The Influence of Service Quality, Trust, and Brand Image on User Satisfaction of BSI Mobile among IAIN Bone Students - Juhasnidar; Rahma Hidayati Darwis; Jumriani (Penerbit Jurnal Indonesia, 2025)
The objective of this study is to examine the influence of service quality, trust, and brand image on user satisfaction of BSI Mobile among students of IAIN Bone. This research adopts a quantitative field study approach. The population includes all IAIN Bone students, with a sample of 99 respondents selected through simple random sampling. The primary data were collected directly from respondents using a Likert scale questionnaire. Data analysis was conducted using IBM SPSS Statistics 25, involving instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and the coefficient of determination (R²) test. The results reveal that service quality significantly and positively affects user satisfaction, as indicated by a significance value of 0.007 (< 0.05). Trust also shows a significant influence on user satisfaction with a value of 0.000 (< 0.05). However, brand image has no significant effect, as shown by a significance value of 0.747 (> 0.05). Simultaneously, service quality, trust, and brand image collectively have a significant impact on user satisfaction, with an overall significance value of 0.000 (< 0.05). These findings indicate that improving service quality and trust can enhance user satisfaction with BSI Mobile, although brand image alone may not be a determining factor.